Dissipating the Earthquake Lateral Base Force of Structure Using Sliding Plate and Link Beam Base Isolation - Argoanto, Yoesoep; Hartono Bagio, Toni; Kusumastuti, Dyah (Universitas Ibn Khaldun Bogor, 2023)
Link beam and sliding plates is used to isolate structure against lateral base shear of the foundation due to earthquake forces, the link beam element made from steel wide flange act as a metallic damper, combined with sliding plates become as base isolation. Analysis with the Etabs program results in significant differences in internal moment, shear and axial forces between structures that using link beam base isolation and those without, as well as the results for drift and deformation of the structure. The first step of analysis is estimate the dimensions of the structural elements. Base on the loads of the structure, the lateral base force of the structure can be calculated manually, so that, by applying the dynamic balance equation, the size of steel wide flange that will be used as the link beam. can be found. Furthermore, the analysis of internal forces, deformation, and structural drifts are calculated using the Etabs program for structural systems that with or without base isolation. The both results are compared so that it can be concluded that by using the base isolation link beam there is a significant decrease in the magnitude of the internal forces, drift and displacement, so that by using this base isolation, the elements of the structure will be reduced significantly, and the cost of structure can be saved, the safety and comfort of the building can be further improved too.